Perbaikan Ketahanan Kedelai terhadap Hama Ulat Grayak - Titik Sundari; Paramita Sari (Iptek Tanaman Pangan, 2015)
Armyworm (Spodoptera litura) is a major pest on soybean. Severe attack of this pest could cause 100% leaf defoliation and harvest failure. Soybean resistant to armyworm follows antibiosis and antixenosis mechanism. Antibiosis resistance was induced by certain chemical substances in the parts of plant that disturbed the physiological and biological processes of pest. Antixenosis resistance was a mechanism by plant morphological barrier that could affect the behavior of pests, such as leaf morphology, especially related to the pubescense density. The availability of soybean variety resistant to armyworm was expected to reduce the use of insecticides and to minimize the harvest failure. Soybean variety resistant to armyworm would be possible to be developed considering the source of genes for resistance had been identified, such as variety Sodendaizu, Himeshirazu, IAC-100, IAC-80-596-2, Bay, and W / 80-2-4- 20. An effective and efficient breeding method had also been available, through repeated backcrosses assisted by DNA markers as selection indicator. IAC-100/Kaba-G-80, IAC-100/Kaba-G-67, IAC-100/Burangrang-P-95, IAC-100/Kaba-G-47, and IAC-100/Burangrang-G-119 were reported as promising lines, having moderately resistance to resistance to the pest, each line derived from the progenies of crossbreeding using IAC 100 as parent.